ANALISIS PENINGKATAN KUALITAS LAYANAN ADMINISTRASI DI SMA - Febrianija Br Tarigan; Jenny Nancy Kaligis; Johny Taroreh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The quality of school administrative services plays an important role in supporting the effectiveness of educational management and the satisfaction of school stakeholders, as it directly affects the smooth implementation of academic and non-academic activities. This study aims to analyze the quality of administrative services, identify the obstacles encountered, and describe efforts to improve services at SMA Negeri 1 Tomohon. The study employed a descriptive qualitative approach using observation, in-depth interviews, and Focus Group Discussions (FGD) for data collection. The research informants consisted of the principal, administrative staff, teachers, students, and parents as users of school administrative services. This approach enabled the researcher to obtain a comprehensive understanding of the actual conditions of administrative services from various perspectives. The findings revealed that the administrative services had been implemented in an orderly, structured, and responsive manner according to users’ needs. However, the main obstacles were the limited optimization of system digitalization, limited human resources, and workload fluctuations that affected service effectiveness during certain periods. Improvement efforts were carried out through regular service evaluations, the development of digital archiving systems, and the enhancement of administrative staff competencies through training. In addition, institutional commitment became an important supporting factor in promoting sustainable service improvement. Therefore, strengthening an integrated digital-based administrative system is a key strategy for creating more effective, adaptive, and user-oriented services in the modern education era. ABSTRAK Kualitas layanan administrasi sekolah memiliki peran penting dalam mendukung efektivitas manajemen pendidikan dan kepuasan warga sekolah karena berpengaruh langsung terhadap kelancaran kegiatan akademik maupun nonakademik. Penelitian ini bertujuan untuk menganalisis kualitas layanan administrasi, mengidentifikasi hambatan yang dihadapi, serta mendeskripsikan upaya peningkatan layanan di SMA Negeri 1 Tomohon. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan Focus Group Discussion (FGD). Informan penelitian terdiri atas kepala sekolah, staf administrasi, guru, siswa, dan orang tua sebagai pengguna layanan administrasi sekolah. Pendekatan ini memungkinkan peneliti memperoleh pemahaman yang komprehensif mengenai kondisi riil pelayanan administrasi dari berbagai perspektif. Hasil penelitian menunjukkan bahwa layanan administrasi telah berjalan cukup tertib, terstruktur, dan responsif terhadap kebutuhan pengguna. Namun, kendala utama masih ditemukan pada belum optimalnya digitalisasi sistem, keterbatasan sumber daya manusia, serta fluktuasi beban kerja yang memengaruhi efektivitas pelayanan pada periode tertentu. Upaya peningkatan dilakukan melalui evaluasi layanan secara berkala, pengembangan sistem pengarsipan digital, dan peningkatan kompetensi tenaga administrasi melalui pelatihan. Selain itu, komitmen kelembagaan menjadi faktor penting dalam mendukung perbaikan layanan secara berkelanjutan. Dengan demikian, penguatan sistem administrasi berbasis digital yang terintegrasi menjadi strategi utama dalam menciptakan layanan yang lebih efektif, adaptif, dan berorientasi pada kebutuhan pengguna di era pendidikan modern.